Contradi(c)ções de um “nego dito”: análise de canções de Itamar Assumpção através da semiótica peirciana - Mendes, Larissa de Souza (2018)
This work intends to analyze songs by Itamar Assumpção according to the General Theory of Signs, by Charles Sanders Peirce. For this, some authors make up the main theoretical base, besides Peirce (1975, 2000), as Lucia Santaella (2000), Winfried Noth (2003) and Expedito Ferraz Junior (2012). The area of theoretical concentration of the present study is Literature, Theory and Criticism, in the research line of semiotic studies. The objectives of this research are: to approach the modes of representation defined by Peirce through their trichotomous classifications, especially with respect to that which characterizes the sign according to the relation that it establishes with its object, classifying it as iconic , indexical or symbolic; make considerations about body and performance in order to better understand the relationship between body, music and orality, and recognize in the figure of the songwriter the fundamental role of sign agglutinator; to approach elements that make up the diction and the work of Itamar Assumpção; Finally, to analyze the modes of representation acting in three songs by Itamar Assumpção - Nego Dito, Luzia and Suicide Visit. The work also has as theoretical support the authors Luiz Tatit (2002; 2004; 2007; 2008) and José Miguel Wisnik (1989); in the analyzes, we bring the studies of Pierre Bourdieux (2002), Paul Gilroy (2012), Heleieth Saffiotti (2001) and Michelle Perrot (2003).